Effects of Inclined Magnetic Field and Porous Medium on Peristaltic Flow of a Bingham Fluid with Heat Transfer - B.B. Divya; G. Manjunatha; C. Rajashekhar; H. Vaidya; K.V. Prasad (Journal of Applied and Computational Mechanics, 2021)
The current paper aims to explain the peristaltic mechanism of a Bingham fluid with varying viscosity. The fluid is considered to flow within a porous medium and subjected to a magnetic field with significant inclination. Heat transfer characteristics are studied with convective conditions and variable thermal conductivity. The solution is obtained by the perturbation technique, where small values of variable liquid properties are utilized. The graphs plotted indicate that variation in viscosity as well as thermal conductivity actively contribute to reduce the pressure gradient. Further, for a higher radius of the plug flow region, a higher pressure rise occurs. The magnetic parameter and Grashof number influence the trapping phenomenon by reducing the dimensions of the bolus.